A novel method for intratracheal injection of infectious agents into mice. (October 2017) - Cheng, Yong; Liepert, Lucas D; Waller, Justin; Leevy, W Matthew; Schorey, Jeff S
Intratracheal injection is a traditional technique used in small animal studies of highly contagious airborne pathogens such as Mycobacterium tuberculosis. However, current techniques of intratracheal injection generally involve procedures that pose a risk of incident injury and infection for researchers, and may also cause collateral damage to experimental animals during the installation process. Here we describe an intratracheal injection method that was enabled by a three dimensional printing of a custom platform. This updated technique improved the overall ergonomics of intratracheal injection in mice, minimizing the risk of human injury and implementing the 3R (replacement, reduction and refinement) principle in mouse infection studies.